Effect of Elbow Position on Short-segment Nerve Conduction Study in Cubital Tunnel Syndrome - Liu, Zhu; Jia, Zhi-Rong; Wang, Ting-Ting; Shi, Xin; Liang, Wei (Chinese medical journal, 2016)
Background： The appropriate elbow position of short-segment nerve conduction study （SSNCS） to diagnose cubital tunnel syndrome （CubTS） is still controversial. The goal of this study was to determine the effect of different elbow positions at full extension and 70° flexion on SSNCS in CubTS. Methods： In this cross-sectional study, the clinical data of seventy elbows from 59 CubTS patients between September, 2011 and December, 2014 in the Peking University First Hospital were included as CubTS group. Moreover, thirty healthy volunteers were included as the healthy group. SSNCS were conducted in all subjects at elbow fhll extension and 70° elbow flexion. Paired nonparametric test, bivariate correlation, Bland-Altman, and Chi-squared test analysis were used to compare the effectiveness of elbow full extension and 70° flexion elbow positions on SSNCS in CubTS patients. Results： Data of upper limit was calculated from healthy group, and abnormal latency was judged accordingly. CubTS group＇s latency and compound muscle action potential （CMAP） of each segment at 70° elbow flexion by SSNCS was compared with lull extension position, no statistically significant difference were found （all P 〉 0.05）. Latency and CMAP of each segment at elbow full extension and 70° flexion were correlated （all P 〈 0 elbow （P - 0.43）, and the latency （P = 0.15） and the CMAP （P = 01）, except the latency of segment of 4 cm to 6 cm above 0.06） of segment of 2 cm to 4 cm below elbow. Bivariate correlation and Bland-Altman analysis proved the correlation between elbow full extension and 70° flexion. Especially in segments across the elbow （2 cm above the elbow and 2 cm below it）, latency at elbow full extension and 70° flexion were strong direct associated（r=0.83, P〈0.01;r=0.55, P〈0.01）,andsodidtheCMAP（r 0.49, P〈0.01;r=0.72, P〈0.01）.Therewasno statistically significant difference in abnormality of each segment at full extension as measured by SSNCS compared with that at 70° flexion （P 〉 0.05, respectively）. Conclusions： There was no statistically significant difference in the diagnosis of CubTS with the elbow at full extension compared with that at 70° flexion during SSNCS. We suggest that elbow positon at full extension can also be used during SSNCS.